Development, Validation and Evaluation of Home-Based Laboratory Worksheets in General Chemistry - Obispo, Kristoffer Paul C.; Ligsanan, Lucky Sonny A. (PT FORMOSA CENDEKIA GLOBAL, 2025)
Home-based laboratory activities are vital for ensuring hands-on learning in remote education, yet challenges like limited resources, student engagement, and safety persist. Despite their benefits, effective instructional materials for college-level General Chemistry in remote settings are lacking. This study develops, validates, and evaluates worksheets designed to support home-based labs, ensuring safe and effective practical work. Results show that the worksheets engage students in learner-centered, experiential learning. Teachers noted their effectiveness in enhancing scientific understanding, despite challenges with material availability and procedural uncertainty. This study provides a model for home-based lab instruction, offering a structured approach to adapt General Chemistry learning for flexible, remote, and resource-limited environments.